PROFILE OF NUTRIENT AND WATER FERTILITY LEVEL AT NUSAWIRU PANGANDARAN WEST JAVA - Ihsan, Yudi Nurul; MS, Yuniarti; Muflihah, Fahira Nuril; Zallesa, Sheila; Fellatami, Kalysta; Pribadi, Tri Dewi K (Jurnal Ilmu Kelautan SPERMONDE, 2022)
Nutrient is one of the most essential elements in the growth and development of marine ecosystem. The aim for this research is to measure the fertility level of Nusawiru Water in Pangandaran West Java. The method used is survey and laboratory analysis using descriptive comparative method. The method used to estimate the level of fertility in this study is the TSI method. The result indicated that the chemical nutrient profile at Nusawiru consists of Ammonia (NH3), Nitrate (NO3-), Nitrite (NO2-), O-Phosphate (PO4). The total amount of Phosphate and chlorophyl shows that the water in the observation station of waste pond, estuary, delta, and open water are in Ultraoligotrophic status. The limiting factor in the waters of Nusawiru Pangandaran is phosphate, because the ratio of N and P at all observation stations are >12.